Analisis Penataan Parkir Alun-Alun Batu di Jalan Diponegoro Kota Batu - Andi Kristafi Arifianto (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2021)
Batu City is one of the cities in EastJava Province which has a tourist destination that is usually visited by immigrants because of its culture, natural beauty and friendly citizens. Located at the intersection of Jalan Diponegoro and Jalan Gajah Mada, Batu City, there is Batu Square which describes one of the holiday destinations in the city center. With this location, and the increasing number of residents, it also increases the need for transportation facilities to support activities, thus causing an increase in the number of 2-wheeled and four-wheeled transportation equipment that requires parking space. With this background, the researcher aims to understand the situation of the existing parking capacity, parking demand, and parking space circulation. To find out, researchers used information in the form of primary data and secondary data. While the results obtained before the pandemic were the number of parking spaces that were still lacking, this was known during the 7-day survey at 15.00 – 21.00, because at that time there were many parked 2-wheeled and 4-wheeled vehicles, so that parking needs exceeded normal capacity. , while the average parking space for motorbikes is 852 parking spaces and the average car parking space is 272 parking spaces, so with this condition it is considered that the parking facilities are not feasible and need to be rearranged. As for the irregular circulation of vehicles, further arrangement is needed.